Achievement of Student Learning Competencies Using Problem Based E-Book in Primary School - Wenni Rahmadani Usri; Yanti Fitria (Tunas: Jurnal Pendidikan Guru Sekolah Dasar, 2023)
Background: This research is motivated by the use teaching materials that are less varied. Aim: The purpose of this study to produce teaching materials in the form of E-Book assisted by Kvisoft Flipbook Maker Pro aplication on natural and social science learning in class IV primary school that are valid, practical, and effective. Results and Dıscussion: This research is a development research (R&D) with the ADDIE model. The ADDIE model consists of analysis, design, development, implementation, and evaluation. The results of validity test of the developed E-Book are 96% for material experts, 96% for media experts, and 94% for linguist with highly valid categoris. The results of the practicality test in the trial school were 94% for teacher responses and 93.21% for student responses. The results of the practicality test in the research school obtained 96% for teacher responses and 96.08% for student responses with very practical categories. The results of the effectiveness test are seen from the N-Gain value, which is 0.72 with a high category. Conclusion: Thus, the use of e-books assisted by the Kvisoft Flipbook Maker Pro application in natural and social science learning in class IV primary schools is declared valid, practical, and effective in learning.